Specyfika i zakres rachunkowości zarządczej projektów - Klinowski, Marcin (Specificity and Range of the Project Management Accounting, 2008)
Management by projects is more and more often applied by companies nowadays. The foregoing paper presents the chosen components of specificity and range of management accounting in project companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 38-43